Migration, Crisis and Temporality at the Zimbabwe–South Africa Border - Vanyoro, Kudakwashe (Bristol University Press, 2026)
Available open access digitally under CC-BY-NC-ND license. Only 15 kilometres away from the border of Zimbabwe, Musina is an obscure town in South Africa that the media cast into the public eye in the wake of the 2008 Zimbabwean economic crisis. Taking as its starting point the arrival of thousands of displaced Zimbabwean migrants at Musina, this book presents valuable new perspectives on the temporality of migration and the governance of immobilities. The author explores the role of humanitarian actors in supporting migrants and examines the outcomes of government-led activities in the longer term. This is an insightful assessment of how state and non-state practices intertwine in the management of largely immobile people, and of the importance of time in understanding African migration and borders.